Orthodontic Compression Enhances Macrophage M2 Polarization via Histone H3 Hyperacetylation - Wang, Yao; Groeger, Sabine; Yong, Jiawen; Ruf, Sabine; Justus Liebig University Giessen (My University, 2023)
Orthodontic tooth movement is a complex periodontal remodeling process triggered by compression that involves sterile inflammation and immune responses. Macrophages are mechanically sensitive immune cells, but their role in orthodontic tooth movement is unclear. Here, we hypothesize that orthodontic force can activate macrophages, and their activation may be associated with orthodontic root resorption. After force-loading and/or adiponectin application, the migration function of macrophages was tested via scratch assay, and Nos2, Il1b, Arg1, Il10, ApoE, and Saa3 expression levels were detected using qRT-PCR. Furthermore, H3 histone acetylation was measured using an acetylation detection kit. The specific inhibitor of H3 histone, I-BET762, was deployed to observe its effect on macrophages. In addition, cementoblasts were treated with macrophage-conditioned medium or compression force, and OPG production and cellular migration were measured. We further detected Piezo1 expression in cementoblasts via qRT-PCR and Western-blot, and its effect on the force-induced impairment of cementoblastic functions was also analyzed. Compressive force significantly inhibited macrophage migration. Nos2 was up-regulated 6 h after force-loading. Il1b, Arg1, Il10, Saa3, and ApoE increased after 24 h. Meanwhile, higher H3 histone acetylation was detected in the macrophages subjected to compression, and I-BET762 dampened the expression of M2 polarization markers (Arg1 and Il10). Lastly, even though the activated macrophage-conditioned medium showed no effect on cementoblasts, compressive force directly impaired cementoblastic function by enhancing mechanoreceptor Piezo1. Compressive force activates macrophages; specifically, it causes M2 polarization via H3 histone acetylation in the late stage. Compression-induced orthodontic root resorption is macrophage-independent, but it involves the activation of mechanoreceptor Piezo1.
Keywords: compressive force; macrophages; polarization; H3 histone; acetylation; adiponectin; ddc:610